Cellulase activity on thermophilic fungi - Azhan, Muhammad Adib (2015)
Thermophilic fungi produce thermostable enzymes which are very stable at extreme and elevated temperature. One of the enzyme produced by thermophilic fungi is cellulase. Interaction of three components of cellulase enzyme in degrading cellulose into its small subunits make cellulase became popular in industrial processes. The sample of thermophilic fungi isolated from hotspring area diluted using serial dilution method grow on potato dextrose agar after incubated at 50℃. The function grow of fungi on potato dextrose agar is to get the single colony of thermophilic fungi. The single colony of thermophilic fungi subcultured into carboxymethyl cellulose agar (CMC) to determine its cellulase production. The fungi identified through macroscopic and microscopic method in order to know the species of fungi. Cellulase comprise of three components which are endoglucanase, exoglucanase and β- glucosidase. The three components of cellulase tested in each specific assay such as filter paper assay, endoglucanase assay and β-glucosidase assay. Filter paper assay determine the total cellulase activity, endoglucanase assay determine endoglucanase activity and β-glucosidase assay determine β-glucosidase activity.